Relações dialógicas no conto neofantástico O homem da cabeça de papelão, de João do Rio - Morais, Ana Célia Santana (2024)
The formation of a critical reader is one of the greatest challenges for teachers, especially in the artisticliterary field, when an interactional approach is taken, exploring activities with the discursive genre of the fantastic realist tale. Thus, based on the organization of reading practices through João do Rio's fantastic short story, The Man with the Cardboard Head, this research aims to investigate the possibilities of carrying out a reading work proposal exploring the ethical-valorative positioning of the author-person, author-creator, narrator, characters, reader and social voices in dialogical relationships. To this end, the research proposes an analysis of the contributions of Bakhtin's (2011, 2016, 2020) and Volóchinov's (2017, 2019) studies that explores the language capacities of valued re-signification according to Carvalho (2021). In the field of reading the discursive genre, we discussed the approach of the fantastic mode, delving into the literary studies of Todorov (2007) who is dedicated to understanding the characterization and effect of the fantastic based on the hesitation between real and unreal, as well as the studies of Alazraki (2001) and Roas (2014) that evoke the understanding of the neofantastic genre. In this context, we developed a reading workshop adopting the principles of dialogic relations and the valued re-signification of the statements expressed by the voices within the text and external discourses present in the social sphere with the reader. Under the evidence of a case study - focused on reading with valued re-signification based on Carvalho (2021, 2023) - which explores the categories of the circle in the process of didactic transposition of literary text reading, the research presents reading activities with a 7th grade elementary school class from a public school in the municipality of Monte Santo-BA. The product of this work is a pedagogical-literary notebook aimed at the active, ethical-discursive and valued understanding contained in João do Rio's short story. Os resultados indicam que o trabalho baseado na teoria de análise das relações dialógicas de Bakhtin contribuiu para uma leitura ativa, responsiva e significativa, auxiliando na formação de um leitor crítico.